Intercultural jokes in a foreign language lesson: A difficult topic to avoid, or an interesting opportunity to reflect on national stereotypes? - Pawłowska-Balcerska, Agnieszka (Glottodidactica, 2022)
The main focus of the article is intercultural jokes as carriers of stereotypes. After discussing the meaning of humour in a foreign language lesson, the concepts of joke and intercultural joke will be explained. Then, an attempt will be made to answer the following questions: Are intercultural jokes in a foreign language lesson a difficult topic that should be avoided, or do they open up an interesting opportunity to consider ethnic and national stereotypes? How can they be incorporated into the teaching and learning process of foreign languages?